2013
DOI: 10.4103/1119-3077.113447
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of impressions with different impression materials in angulated implants

Abstract: On the basis of the results of this study, the use of both the impression materials i.e., polyether and polyvinyl siloxane impression is recommended for impression making in parallel as well as angulated implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…[ 26 ] The gingival health was checked using periodontal probe before every gingival displacement. [ 27 ] It has been reported in previous studies[ 27 28 ] that the health of the gingival tissue returns to optimum when examined after 8 days of gingival displacement.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] The gingival health was checked using periodontal probe before every gingival displacement. [ 27 ] It has been reported in previous studies[ 27 28 ] that the health of the gingival tissue returns to optimum when examined after 8 days of gingival displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Reddy, Karl showed little or no difference between polyether and polyvinyl siloxane when using a direct technique , . 30,31 Considering rotational transfer precision of implants in the present study, it was conceived that with direct (open tray) impression technique, polyether result in less discrepancy compared to polyvinyl siloxane. We 32 reported that for completely edentulous multipleimplant restorations, the use of polyether showed the best results .…”
Section: Discussionmentioning
confidence: 96%
“…[ 11 ] advised open-tray impression technique and PE and PVS imprint materials for precise results, Reddy et al . [ 12 ] discovered comparable dimensional accuracy for transfer techniques.…”
Section: Discussionmentioning
confidence: 99%